2021
DOI: 10.1155/2021/6665829
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Accuracy of an FDR Sensor in Soil Moisture Measurement under Laboratory and Field Conditions

Abstract: Soil water content (SWC, % vol) is a key factor affecting plant growth and development. SWC measurement is vital to rational use of water resources for irrigation, and the accuracy of sensors in SWC measurement is of significant importance to smart data-driven irrigation. Here, a laboratory experiment and a field lysimetric experiment were conducted to evaluate the accuracy of Insentek sensors under various soil conditions (1.1 to 1.5 bulk densities and sand to clay soil textures) and irrigation levels (30, 45… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 29 publications
(38 reference statements)
0
5
0
Order By: Relevance
“…Our previous study indicated that the Insentek sensor was a reliable tool to represent real SWC values in the field with a root mean square error (RMSE) of 0.927% v/v between the Insentek sensor and oven-dry method (Table S1) [36]. Through checking the year-round data, data of Insentek sensors also had good continuity and stability [5]. Crops around the sensors were not missed and uniform, and were representative of the experimental conditions with the similar sizes and vigor.…”
Section: Soil Water Content and Crop Evapotranspirationmentioning
confidence: 97%
See 1 more Smart Citation
“…Our previous study indicated that the Insentek sensor was a reliable tool to represent real SWC values in the field with a root mean square error (RMSE) of 0.927% v/v between the Insentek sensor and oven-dry method (Table S1) [36]. Through checking the year-round data, data of Insentek sensors also had good continuity and stability [5]. Crops around the sensors were not missed and uniform, and were representative of the experimental conditions with the similar sizes and vigor.…”
Section: Soil Water Content and Crop Evapotranspirationmentioning
confidence: 97%
“…A center pivot irrigation system (CPIS) is considered adaptable in the mechanized operation for both wheat and maize due to its adaptability to different crops [4]. In addition, due to the over-depletion of aquifers, the NCP has become the severest groundwater depression zone in the world [5]. This especially expedites the development of water-saving techniques, making precision irrigation an inevitable trend for future agriculture in this area.…”
Section: Introductionmentioning
confidence: 99%
“…One study found that more accurate estimations for weekly citrus tree irrigation were obtained when soil sensor data was combined with weather information. In this part, we'll take a look at several different types of SMS-enabled smart irrigation systems (Qin, et al, 2021).…”
Section: Soil Moisture-based Irrigation Managementmentioning
confidence: 99%
“…The water balance in the soil and the need for crop irrigation can be estimated by measuring the SMC (Qin et al, 2021). Several studies have reported on irrigation monitoring based on soil moisture sensing (Blessy, 2021; Hamouda et al, 2021; Wang et al, 2021).…”
Section: Smart Strategies For Precision Irrigationmentioning
confidence: 99%